2018
DOI: 10.1002/cbf.3322
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the molecular mechanism and apoptosis underlying the in‐vitro and in‐vivo chemotherapeutic efficacy of vanadium luteolin complex in colon cancer

Abstract: The present study demonstrates that the effect of vanadium-luteolin complex in HT-29 cells and dimethylhydrazine challenged rats, curtail cell proliferation through induction of apoptosis mediated via activation of the key proteins involved in the intrinsic pathway like p53, Bax, caspase-3 and downregulating Bcl2, mTOR/Akt, angiogenic factor VEGF along with aberrant crypt foci formation multiplicity, and PCNA in the colon mucosa. Our combinatorial approach shows higher efficacy at considerably lower doses mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Among vanadium compounds V 2 O 5 is highly toxic (Naso et al, 2016) but the oxidovanadium/luteolin complex (Roy & Chakraborty, 2018) or vanadium/luteolin complex (Pfeffer & Singh, 2018) are also inducers of apoptosis via activation of p53, Bax and caspase-3, key proteins involved in the intrinsic pathway (Weigel et al, 2014). Our results with NaVO 3 showed that none of the intrinsic or extrinsic molecules was significantly modified, as the final pathways products, caspase-3 and/or caspase-7, remained unaltered independently of the treatment time.…”
Section: Discussionmentioning
confidence: 99%
“…Among vanadium compounds V 2 O 5 is highly toxic (Naso et al, 2016) but the oxidovanadium/luteolin complex (Roy & Chakraborty, 2018) or vanadium/luteolin complex (Pfeffer & Singh, 2018) are also inducers of apoptosis via activation of p53, Bax and caspase-3, key proteins involved in the intrinsic pathway (Weigel et al, 2014). Our results with NaVO 3 showed that none of the intrinsic or extrinsic molecules was significantly modified, as the final pathways products, caspase-3 and/or caspase-7, remained unaltered independently of the treatment time.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, V-quercetin induces apoptosis and inhibits cancer cell growth associated with the anti-angiogenic pathway [31] . Similarly, the Ru-quercetin, V-luteolin, and Ru-chrysin complexes induce cancer cells to undergo apoptotic cell death by activating p53 through activation of apoptotic factor Bax and caspase-3 while inhibiting the mTOR/Akt pathway [32][33][34][35] . Lanthanum (III), a rare-earth metal, forms a complex with quercetin which binds to DNA, inhibits tumor cells better than quercetin does [36] .…”
Section: Formation Of Tcm-metal Complexesmentioning
confidence: 99%
“…Quercetin, Luteolin, Chrysin, Baicalein Induces cell cycle arrest and induces apoptosis by upregulating p53, caspase-3, caspase-9 and Bax, followed by down-regulating Bcl-2, VEGF, mTOR and Akt [31][32][33][34][35] La 3+ Quercetin Inhibits the proliferation of cancer cells by binding to DNA [36] Cu 2+ Myricetin, taxifolin, morin, kaempferol Such complexes promote the formation of ROS and kill cancer cells by causing DNA damage [37][38] Zn 2+ , Fe 2+ Carboxymethyl pachymaran…”
Section: Ni 2+ Curcuminmentioning
confidence: 99%
“…Additionally, luteolin inhibits expression of the cyclic AMP (cAMP) response element‐binding protein 1 (CREB1) at the transcriptional level, which involves in blockage of epithelial‐to‐mesenchymal transition of colorectal cells (Liu et al, ). Moreover, in vitro and in vivo results of a recent study demonstrated the proapoptotic effects of vanadium‐luteolin complex in HT‐29 cancer cells and dimethylhydrazine (DMH) challenged rats which was mediated through activation of p53, Bcl2‐associated X protein (Bax), and caspase‐3 and downregulation of B‐cell lymphoma 2 (Bcl2), mTOR/Akt angiogenic factor vascular endothelial growth factor (VEGF), and proliferating cell nuclear antigen (PCNA) in the colon mucosa (Roy & Chakraborty, ).…”
Section: Flavonoid Categories With Preventive and Therapeutic Effect mentioning
confidence: 99%